YPEL1 overexpression in early avian craniofacial mesenchyme causes mandibular dysmorphogenesis by up‐regulating apoptosis. Issue 8 (16th July 2015) - Tan, Tiong Yang; Gordon, Christopher T.; Miller, Kerry A; Amor, David J.; Farlie, Peter G.
Abstract : Background: The YPEL ( Yippee‐like ) gene family comprises five highly conserved members ( YPEL1‐5 ), but their biological function remains largely unknown. Early studies of YPEL1 function suggested that it plays a role in the development of structures derived from the pharyngeal arches. Human YPEL1 localises to distal chromosome 22q11.2 and copy number changes at this locus lead to diverse phenotypes that include facial dysmorphism, facial asymmetry, and palatal anomalies comprising the distal 22q11.2 deletion/duplication syndromes (OMIM 611867). We therefore investigated the role of chick YPEL1 in craniofacial development using ex vivo and in vivo approaches in the avian model. Results: We found that retroviral‐mediated in vivo overexpression of YPEL1 causes abnormal mandibular morphogenesis associated with increased apoptosis and involvement of the BMP / MSX pathway. Conclusions: Our results suggest that YPEL1 expression is regulated by bone morphogenetic protein signaling and suggest a role for YPEL1 in the pathogenesis of the craniofacial abnormalities observed in humans with distal chromosome 22q11.2 deletions or duplications. Developmental Dynamics 244:1022–1030, 2015 . © 2015 Wiley Periodicals, Inc. Key Findings: Over‐expression of YPEL1 causes chick mandibular hypoplasia due to up‐regulation of apoptosis. Timing of infection was critical and affected penetrance of the mandibular phenotype, suggesting a temporal sensitivity to YPEL1 over‐expression. Apoptosis was not up‐regulated in infected limb structures suggesting tissue‐specificity and not just a general retroviral‐infection phenomenon. These findings suggest that YPEL1 is dosage‐sensitive and may play a role in the pathogenesis of craniofacial anomalies observed in human distal chromosome 22q11 syndromes (OMIM 611867)